Estudo experimental do peneiramento vibratório em batelada de suspensão diluída de rocha fosfática: determinação do teor de umidade de material retido, eficiência granulométrica e diâmetro de corte - Guerreiro, Fernando Superbi (2015)
The detailed study of the screen operation considering cause and effect amongst several involved operational variables takes a prominent position regarding the solid-liquid separation. The general objective of this dissertation was the initial study of the vibrating screening that can be extended to the solid control in drilling rigs and the specific goal of this work was to assess the effects of screen aperture, volumetric concentration of solids in the feed and vibration (or g-force) upon the moisture of the retained material, the overall granulometric e fficiency of separation and the cut diameter by using a suspension of phosphatic rock and xanthan gum diluted in water. An experimental design 3k was created to execute the experiments, where the screen apertures were 95, 106 and 130 µm, volumetric concentration of solids in the feed 1, 2 and 3% and g-force of magnitude 1.00, 2.25 and 3.50. For the performance of the experiments, a pilot scale vibrating screen was used that processed 159 liters in 18 minutes. The results showed that the minimum moisture was obtained with the screen of 95 µm, volumetric concentration of 1% and vibration of magnitude 1.0 g, whereas for the overall granulometric efficiency the maximum condition was with 106 µm screen aperture, concentration of 1% and vibration of 1.0 g. The optimal point covering high efficiency and low moisture was achieved with 95 µm screen aperture, volumetric concentration between 2 and 3% and the least intense vibration(1.0 g). For the cut diameter the results obtained for each screen showed that its value decreased with the use of more intense vibration. The results obtained in the developed work are important to understand the main operational aspects in the solid-liquid separation by using shale shakers.